Sympatry influence in the interaction of Trypanosoma cruzi with triatomine - Elaine Schultz Dworak; Silvana Marques de Araújo; Mônica Lúcia Gomes; Miyoko Massago; Érika Cristina Ferreira; Max Jean de Ornelas Toledo (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Trypanosoma cruzi, the etiologic agent of Chagas disease, is widely distributed in nature, circulating between triatomine bugs and sylvatic mammals, and has large genetic diversity. Both the vector species and the genetic lineages of T. cruzi present a varied geographical distribution. This study aimed to verify the influence of sympatry in the interaction of T. cruzi with triatomines. Methods: The behavior of the strains PR2256 (T. cruzi II) and AM14 (T. cruzi IV) was studied in Triatoma sordida (TS) and Rhodnius robustus (RR). Eleven fifth-stage nymphs were fed by artificial xenodiagnosis with 5.6 × 103 blood trypomastigotes/0.1mL of each T. cruzi strain. Every 20 days, their excreta were examined for up to 100 days, and every 30 days, the intestinal content was examined for up to 120 days, by parasitological (fresh examination and differential count with Giemsa-stained smears) and molecular (PCR) methods. Rates of infectivity, metacyclogenesis and mortality, and mean number of parasites per insect and of excreted parasites were determined. RESULTS: Sympatric groups RR+AM14 and TS+PR2256 showed higher values of the four parameters, except for mortality rate, which was higher (27.3%) in the TS+AM14 group. General infectivity was 72.7%, which was mainly proven by PCR, showing the following decreasing order: RR+AM14 (100%), TS+PR2256 (81.8%), RR+PR2256 (72.7%) and TS+AM14 (36.4%). CONCLUSIONS: Our working hypothesis was confirmed once higher infectivity and vector capacity (flagellate production and elimination of infective metacyclic forms) were recorded in the groups that contained sympatric T. cruzi lineages and triatomine species.